Writing Palestine 1933-1950 - Bar-Adon, Dorothy Kahn (Academic Studies Press, 2016)
From her immigration to Mandatory Palestine in 1933 until her death in 1950 American-born Dorothy Kahn Bar-Adon worked as a reporter for The Palestine Post (later The Jerusalem Post), while freelancing for periodicals in Palestine and abroad. Bar-Adon covered life in towns, kibbutzim and Arab communities of Mandatory Palestine during this period of World War, armed conflict between Arabs and Jews, immigration to Israel of Holocaust survivors. Close to 60 years after her death, this edited collection of Bar-Adon's writing offers a vivid view both of daily life in the Jewish and Arab communities of pre-State Israel, and of the burning issues of the day.